Torrefaction of biomass for energy applications : from fundamentals to industrial scale - Nunes, Leonel Jorge Ribeiro (Academic Press, 2018)
"[E]xplores the processes, technology, end-use and economics involved in torrefaction at industrial scale for heat and power generation. Its authors combine their industry experience with their academic expertise to provide a thorough overview of the topic. Starting at feedstock pretreatment, followed by torrefaction processes, the book includes plant design and operation, safety aspects and case studies focusing on the needs and challenges of industrial scale. Commercially available technologies are examined and compared, and their economical evaluation and life cycle assessments are covered as well. Attention is also given to non-woody feedstock, alternative applications, derived fuels, recent advances and expected future developments"--Back cover